Which variables influence the herbivory amount on Montrichardia spp. (Araceae) in aquatic ecosystems? - Fares, Ana Luisa Biondi; de Carvalho, Wendell Vilhena; Michelan, Thaisa Sala; Teodoro, Grazielle Sales (Revista de Biología Tropical, 2022)
Introduction: The study of herbivory is fundamental in ecology and includes how plants invest in strategies and mechanisms to reduce herbivore damage. However, there is still a lack of information about how the environment, plant density, and functional traits influence herbivory in aquatic ecosystems. Objective: To assess if there is a relationship between herbivory, environmental variables, and plant traits two species of Montrichardia, a neotropical aquatic plant. Methods: In September 2018, we studied 78 specimens of Montrichardia arborescens and 18 of Montrichardia linifera, in 18 sites in Melgaço, Pará, Brazil. On each site, we measured water depth, distance to the margin, and plant density. From plants, we measured plant height and leaf thickness, and photographed the leaves to calculate the specific leaf area and percentage herbivory. To identify anatomical structures, we collected fully expanded leaves from three individuals per quadrat. Results: For M. arborescens, plants with thicker leaves and higher specific leaf area have less herbivore damage. For M. linifera, plants from deeper sites and with thicker leaves had more herbivore damage, while plants that grew farther from the margin had less damage. We found anatomical structures related to defense, such as idioblast cells with phenolic compounds, and cells with solid inclusions that can contribute to avoiding severe damage. Conclusions: Herbivory in these Montrichardia species canbe explained by a combination of plant and environmental traits (patch isolation and water depth). The main plant traits are leaf thickness and area, but chemical compounds and solid inclusions also help Montrichardia to sustain less damage than other macrophytes.